2018
DOI: 10.1007/978-1-4939-8597-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol-Induced Heart Failure Mouse Model Using Osmotic Pump Implantation

Abstract: Isoproterenol is used widely for inducing heart failure in mice. Isoproterenol is a nonselective beta-adrenergic agonist. The acute model mimics stress-induced cardiomyopathy. The chronic model mimics advanced heart failure in humans. In this chapter, we describe a protocol that we used to induce heart failure in 100+ strains of inbred mice. Techniques on surgical pump implantation and echocardiography are described in detail. We also discuss the impact of drug dosage, duration, mortality, age, gender, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 20 publications
3
58
0
Order By: Relevance
“…Third, isoprotenerol infusion effectively induced HF. As expected from extensive data in the literature (6), mice in the HF groups had significant increases in LVEDD and LVESD as well as significant reductions in LVEF and FS (Figure 1). Indeed, 2-way ANOVA of the 4 groups showed that HF was significant (p = 0.013, 0.006, p = 0.027, and p = 0.047 for LVEDD, LVESD, LVEF, and FS, respectively).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Third, isoprotenerol infusion effectively induced HF. As expected from extensive data in the literature (6), mice in the HF groups had significant increases in LVEDD and LVESD as well as significant reductions in LVEF and FS (Figure 1). Indeed, 2-way ANOVA of the 4 groups showed that HF was significant (p = 0.013, 0.006, p = 0.027, and p = 0.047 for LVEDD, LVESD, LVEF, and FS, respectively).…”
Section: Resultssupporting
confidence: 82%
“…HF was conventionally induced by continuous infusion of isoproterenol (6). Briefly, mice in HF and HF+SF groups were anesthetized by isoflurane inhalation and an osmotic mini-pump (Alzet, model 1004) was implanted subcutaneously in the flank.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the ß-adrenergic agonist isoproterenol to induce cardiomyocyte necrosis has been described over 50 years ago in rats 19,20 and has been characterised extensively. 21,22 It now routinely serves as a long-term low-dose treatment to induce cardiac hypertrophy, [23][24][25] and few research groups have also used it to induce acute infarct-like necrotic lesions by injection of high doses. [26][27][28] Importantly, the isoproterenol model recapitulates several of the salient features of T2MI.…”
Section: Introductionmentioning
confidence: 99%
“…Isoproterenol is a nonselective beta-adrenergic agonist inducing early cardiac hypertrophy and hypercontractility followed by HF with cardiac dilation and ventricular dysfunction secondary to by chronic adrenergic overstimulation [ 9 ]. The diaphragm contractility enhancement we report here for the first time in the conventional isoproterenol-induced HF model was hypothesized based on previous indirect data on the effects of this nonselective beta-adrenergic agonist in non-cardiac muscles.…”
Section: Discussionmentioning
confidence: 99%
“…HF was induced by continuous infusion of isoproterenol with an osmotic pump, following the conventional procedure in this model [ 9 ]. Briefly, mice were anesthetized with a mixture of inhaled isoflurane and oxygen-enriched air (1.25% during induction and 1% during maintenance) and a small incision was made on the back of each animal between the shoulder blades after removing the hair from the area using depilatory cream.…”
Section: Methodsmentioning
confidence: 99%